Longitudinal changes in adherence to the portfolio and DASH dietary patterns and cardiometabolic risk factors in the PREDIMED-Plus study. Issue 5 (May 2021) - Glenn, Andrea J.; Hernández-Alonso, Pablo; Kendall, Cyril W.C.; Martínez-González, Miguel Ángel; Corella, Dolores; Fitó, Montserrat; Martínez, J.Alfredo; Alonso-Gómez, Ángel M.; Wärnberg, Julia; Vioque, Jesús; Romaguera, Dora; López-Miranda, José; et al.
Summary: Background & aims: The Portfolio and Dietary Approaches to Stop Hypertension (DASH) diets have been shown to lower cardiometabolic risk factors in randomized controlled trials (RCTs). However, the Portfolio diet has only been assessed in RCTs of hyperlipidemic patients. Therefore, to assess the Portfolio diet in a population with metabolic syndrome (MetS), we conducted a longitudinal analysis of one-year data of changes in the Portfolio and DASH diet scores and their association with cardiometabolic risk factors in Prevención con Dieta Mediterránea (PREDIMED)-Plus trial. Methods: PREDIMED-Plus is an ongoing clinical trial (Trial registration: ISRCTN89898) conducted in Spain that includes 6874 older participants (mean age 65 y, 48% women) with overweight/obesity fulfilling at least three criteria for MetS. Data for this analysis were collected at baseline, six months and one year. Adherence to the Portfolio and DASH diet scores were derived from a validated 143-item food frequency questionnaire. We used linear mixed models to examine the associations of 1-SD increase and quartile changes in the diet scores with concomitant changes in cardiometabolic risk factors. Results: After adjusting for several potential confounders, a 1-SD increase in the Portfolio diet score was significantly associated with lower HbA1c (β [95% CI]: −0.02% [−0.02, −0.01], P < 0.001), fasting glucose (−0.47 mg/dL [−0.83, −0.11], P = 0.01), triglycerides (−1.29 mg/dL [−2.31, −0.28], P = 0.01), waist circumference (WC) (−0.51 cm [−0.59, −0.43], P < 0.001), and body mass index (BMI) (−0.17 kg/m 2 [−0.19, −0.15], P < 0.001). A 1-SD increase in the DASH diet score was significantly associated with lower HbA1c (−0.03% [−0.04, −0.02], P < 0.001), glucose (−0.84 mg/dL [−1.18, −0.51], P < 0.001), triglycerides (−3.38 mg/dL [−4.37, −2.38], P < 0.001), non-HDL-cholesterol (−0.47 mg/dL [−0.91, −0.04], P = 0.03), WC (−0.69 cm [−0.76, −0.60 cm], P < 0.001), BMI (−0.25 kg/m 2 [−0.28, −0.26 kg/m 2 ], P < 0.001), systolic blood pressure (−0.57 mmHg [−0.81, −0.32 mmHg], P < 0.001), diastolic blood pressure (−0.15 mmHg [−0.29, −0.01 mmHg], P = 0.03), and with higher HDL-cholesterol (0.21 mg/dL [0.09, 0.34 mg/dL, P = 0.001]). Similar associations were seen when both diet scores were assessed as quartiles, comparing extreme categories of adherence. Conclusions: Among older adults at high cardiovascular risk with MetS, greater adherence to the Portfolio and DASH diets showed significant favourable prospective associations with several clinically relevant cardiometabolic risk factors. Both diets are likely beneficial for cardiometabolic risk reduction.